Without passage - Chee, En Cui (Nanyang Technological University, 2021)
Aporia (ᾰ̓πορῐ́ᾱ "lacking passage") — a state of puzzlement, a declaration of doubt. This project explores the relation of aporia & epiphany, in moving to a state of certainty from a state without, and offers an opinion on syntactic (form) versus semantic (meaning) epiphanies.